Continuity of operations planning for academic institutions - Henderson, Douglas M. (Henry Stewart Talks, 2011)
Planning and development, Information gathering, Analysis, Risk identification, assessment and treatment, Command and Control issues, Relationships and responsibilities, Crisis communication, Planning for students, Recovery from a major disaster, Emergency response plan and procedures, Hazard specific emergencies, Actions that should occur automatically, Interfacing with civil responders, Maintenance